1989
DOI: 10.1111/j.1468-2958.1989.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Arousal and Nonverbal Indices

Abstract: Thecurrent monographasserts that nonverbal behaviorscan serveas usefulovert indices of experienced arousal. Various conceptualizutions of arousal and factors eliciting arousnl in communication situations are examined. It is proposed that, from a communicntion standpoint, indices of arousal and arousal change are best classijied along two dimensions of arousal intensity and arousal valence. Diverse bodies of literature on nonverbal coiicornitaii ts ojarousnlare reviewed. As afirst test ofwhether separate profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 129 publications
5
45
2
Order By: Relevance
“…Sparks, Greene / MEASURING PHYSlOLOGICAL AROUSAL 469 2. Our manipulation of involvement differed from the one reported by Burgoon et al (1989) in several respects. First, we employed a conversational confederate from the outset, whereas Burgoon et al recruited one of the naive partiapants to act as a confederate during the second phase of the study.…”
Section: Resultscontrasting
confidence: 59%
“…Sparks, Greene / MEASURING PHYSlOLOGICAL AROUSAL 469 2. Our manipulation of involvement differed from the one reported by Burgoon et al (1989) in several respects. First, we employed a conversational confederate from the outset, whereas Burgoon et al recruited one of the naive partiapants to act as a confederate during the second phase of the study.…”
Section: Resultscontrasting
confidence: 59%
“…First is the matter of nonlinear relationships. As noted earlier, Burgoon et al (1989) tested and confirmed numerous nonlinear relationships between specific nonverbal behaviors and global arousal. (Le Poire's, 1991, experiment and one by Burgoon et al, 1991, in which nonverbal arousal indices were validated in a psychotherapeutic context, subsequently also found curvilinear relationships.)…”
Section: Errors In the Sparks And Greene Investigationsupporting
confidence: 56%
“…To protect against measurement-induced multicollinearity, different pairs of coders were responsible for separate blocks of behavior, which further increased the independence of ratings across the various subsets. Thus we feel confident that the Burgoon et al (1989) findings can be trusted.…”
Section: Errors In the Sparks And Greene Investigationmentioning
confidence: 88%
“…Movements by the participants can increase their level of arousal, and such movements were indeed observed in the videorecordings during some blaming moments. However, preparing to act causes the level of arousal to rise before the actual body movement (Burgoon et al 1989). Self-touching has also been linked to emotion regulation (Grunwald et al 2014;Ekman and Friesen 1969), and thus observations of hand movements may rather enrich the analysis than interfere with the findings.…”
Section: Discussionmentioning
confidence: 99%